Capacity Building of the Regional Inspectorate of the Sangihe Islands Regency - Boham, Jeane; Dilapanga, Abdul Rahman; Bulo, Laurens (Technium Social Sciences Journal, 2025)
The purpose of this study was to determine, analyze and describe the strengthening of the PPUPD and Auditor apparatus at the Regional Inspectorate of the Sangihe Islands Regency. This research uses a qualitative approach. The results showed that apparatus development at the Regional Inspectorate of the Sangihe Islands Regency was carried out through programs, activities and sub-activities that focused on increasing competence in accordance with regulations, such as Decree of the Minister of Home Affairs Number 893.4-2018 of 2022 and BPKP Regulation Number 5 of 2023. This program includes orientation, leveling, technical substance training, as well as other developments such as in-house training, mentoring, and seminars. However, the implementation of this program faces significant obstacles, including limited funding, supervisory planning that is not yet risk-based, vacant structural positions, and a lack of PPUPD and Auditor functional personnel. These obstacles have an impact on increasing workload, low levels of participation in training, and limited time for apparatus development. Factors affecting apparatus development include leadership commitment, technological advances, organizational complexity, work facilities, as well as motivation, and work environment support. Strengthening strategies include meeting training needs of at least 120 hours per year, filling vacant positions, applying technology such as e-audit applications, and developing needs-based competency maps. The results of this study emphasize the importance of leadership commitment, technological support, and synergy between apparatus to achieve sustainable development and support the improvement of supervisory quality in the Regional Inspectorate.